Fracture toughness of cemented carbides: Testing method and microstructural effects. (March 2015) - Sheikh, Saad; M'Saoubi, Rachid; Flasar, Petr; Schwind, Martin; Persson, Tomas; Yang, Jing; Llanes, Luis
Abstract: Fracture toughness is one the most important parameters for design applications and performance assessment of WC–Co cemented carbides (hardmetals). Different from hardness, fracture toughness is commonly a property more difficult to evaluate, particularly in brittle materials. A large number of different testing methods have been introduced to evaluate toughness of hardmetals, but in general all of them have either theoretically debatable issues or important experimental difficulties. In this study, three different fracture toughness testing methodologies are investigated: three-point bending on Chevron notched specimen ("reference" baseline), Palmqvist indentation test, and Hertzian indentation method. The work is conducted in several cemented carbide grades with different microstructures, in terms of both WC grain size and Co binder content. It is found that Chevron-notched three-point bending test yields suitable fracture toughness values for a wide range of cemented carbide grades with varying hardness. Concerning indentation methods, the Hertzian one may be particularly recommended, as compared to Palmqvist method, as far as hardness (HV30) drops below 1300. On the other hand, if HV30 is higher than 1300 Palmqvist indentation procedure yields reliable fracture toughness measurements. Experimental findings are finally analyzed and discussed on the basis of two theoretical models proposed in the literature. Highlights: Microstructural characterization, using EBSD, for nine hardmetal grades with wide ranges of grain size and cobalt content. Fracture toughness assessment through Chevron-notched three-point bending, Palmqvist and Hertzian indentation tests. Correlation of microstructural parameters (determined from EBSD analysis) with hardness and fracture toughness. Comparison of experimental (from Chevron notched specimens) and estimated (from theoretical models) toughness values.